Digital of Education: An overview Transformation - Vyas, Komal (International Journal of Psychosocial Rehabilitation, 2020)
This research paper analyses the importance of digital transformation of education at several levels by giving quality to education. It optimised the available resources, gives productivity to the man-power and meet the today’s demand. It includes providing digital means for communication between students. Digital transformation is not a one-time event. It proceeds in waves driven by technologies and innovations. The immense breadth of technologies and their possible applications favours a fragmentation of research across which a holistic view is missing. The findings here indicate that education is benefitted to the extent as digitalisation helps in improving overall quality performances from one sector to the other by management, collection, interpretation and transmission of information digitally. It becomes important in every field. It helps in discovering new solutions to an organization. This makes possible to realize innovations faster and more reliable. Education industry completely transformed by the digitalization.